Measuring the differences in the students’ academic self-concept according to the educational levels of the LMD system - Benchouita, Belkacem (Journal of Human Sciences, 2021)
This study aimed to measure the differences in the academic self-concept of students according to the educational levels of the LMD system, and the researcher followed the descriptive approach, where the research sample included (48) students distributed over three levels (second year BA, second year Master And the second year is a Ph.D.), and the researchers used the academic self-concept scale consisting of (30) items, and after applying the tool to the members of the research sample and processing the results by the statistical package (spss) program, the results resulted in: - The existence of statistically significant differences in the degree of academic self-concept of graduating students according to the academic level of the LMD system and in favor of doctoral students